CRACK FAULT DIAGNOSIS OF ROTOR BASED ON VMD AND AR MODEL - ZHONG ZhiXian; JIAO BoLong; WANG JiaYuan; LIU YiXin; ZHU ChangSheng (Jixie qiangdu)
Aiming at the vibration displacement signals of cracked rotors is unstable and non-linear,and the fault features are extracted difficultly,and the sample collection is lacking in the initial stage of fault,the crack fault diagnosis method based on Variational Mode Decomposition and AR model is proposed. A number of Intrinsic Mode Function are obtained by VMD as the preprocessing of the AR model. The AR model for each IMF component is established. The variance of the model parameters and residuals is calculated by the least square method. The model parameters and the variance of the residual are used as the characteristic vector of the system state. From the Mahalanobis distance and setting the corresponding weighted parameters,the synthetic distance is used to diagnose crack fault of rotor. Through the analysis of the experimental data,the feasibility of the fault diagnosis method based on the variational mode decomposition and the AR model are successfully verified,which provides a method for the fault diagnosis of the rotor,and the shortcomings of AR model in the diagnosis of rotor crack fault are overcome.